The Logic of Vertical Restraints - Rey, Patrick; Tirole, Jean (American Economic Review, 1986)
This paper shows that direct (product) competition acts as a tournament between retailers when informational problems (or transaction costs) prevent the manufacturer from using contracts based on their relative performances. Anticompetitive restraints such as exclusive territories and resale price maintenance (which, we show, are not necessarily good substitutes) may or may not be privately desirable. It also shows that privately desirable anticompetitive restraints may not be socially desirable.